Comparison of techno-functional and sensory properties of sponge cakes made with egg powder and different quality of powdered blood products for substituting egg allergen and developing functional food - Csurka, Tamás; Varga-Tóth, Adrienn; Kühn, Dorottya; Hitka, Géza; Badak-Kerti, Katalin; Alpár, Boglárka; Surányi, József; Friedrich, László Ferenc; Pásztor-Huszár, Klára (Frontiers in Nutrition, 2022)
Animal blood is a valuable resource, which is usually not utilized in a value-added way by the industry like other animal by-products, even though it has plenty of benefits in terms of sustainability and human health, particularly against iron deficiency anemia. Animal blood is perfectly suitable for providing special functions, which are necessary for functional foods, and improving techno-functional properties based on the previous reports published in the literature. In this paper, egg powder was substituted by powdered animal blood products (whole blood powder, blood plasma powder, and hemoglobin powder) in sponge cake. Techno-functional and sensory properties (texture by texture profile analysis and three-point breaking test, water activity, dry matter content, and color) were instrumentally measured and then a sensory evaluation was carried out by unskilled panelists. Quality characteristics (texture, color, and dry matter content) were daily measured on the day of baking and then every 24 h for 3 additional days because freshly baked cakes are usually consumed within 3 days. Based on the results, powdered blood products are suitable for substituting the egg powder in sponge cakes and developing functional foods. Blood powders can increase the hardness, chewiness, and breaking force of cakes, giving them the ability to be stuffed with more fillings and molded into special shapes without compromising on the sensory characteristics. They can also increase the intensity of the cocoa flavor, which results in a richer, darker color without deceiving the consumers.